The Mediating Effect of Brand Image on the Influence of Electronic Word of Mouth Towards Purchase Intention for Somethinc Products (Case Study on Followers of the @somethincofficial TikTok Account) - Fellysia, Fellysia; Simamora, Bilson (AIBPM Publisher, 2023)
Social media is an appropriate platform for conveying electronic word of mouth related to products, services, and brands to other users. One of the social media that can generate electronic word of mouth is TikTok. Conceptually, experts say electronic word-of-mouth (e-WOM) communication can influence a company's brand image and consumer purchase intentions. However, e-WOM research via Tiktok is still limited in Indonesia. Therefore, to conduct such research, the researchers judgementally recruited 183 respondents as the sample. Using Structural Equation Modeling (SEM) with WarpPLS version 8.0 for data analysis, the researchers found that electronic word of mouth positively affects brand image. Furthermore, electronic word of mouth has a positive and significant effect on purchase intention, and brand image has a positive and significant effect on purchase intention. Moreover, brand image mediates the effect of electronic word of mouth on purchase intention. Future researchers are suggested to use other social media such as Instagram, Facebook, and Twitter.